Utilizing target capture sequencing to resolve the speciation history of Echinacea (Asteraceae) - Jordan, Chazz; Leebens-Mack, James H. (Frontiers in Plant Science, 2025)
It has been difficult to resolve relationships among many important lineages within the Asteraceae family due to interspecific hybridization and rapid species diversification throughout the history of the family. Previous efforts to resolve evolutionary relationships among Echinacea species have relied heavily on variation in the plastid genome with limited analysis of nuclear loci. In this study, we combine whole plastome sequences and nuclear gene capture data to reconstruct species relationships and characterize the pace of speciation across the genus Echinacea. With more sampling of intraspecific variation in both the plastome and nuclear sequence data, we find evidence for interspecific gene flow and reject the previously hypothesized early split between Echinacea lineages, including species with ranges centered in the eastern and midwestern U.S. At the same time, we find evidence for rapid radiation early in the history of Echinacea in agreement with previous studies. Our findings have implications for Echinacea conservation and trait evolution in the genus.